STUDY OF THE IMPACT OF SAND PENETRATION ON PUMPING EQUIPMENT OPERATION MODES IN THE KIZILKUM REGION CONDITIONS - Qurbonov Oybek Muxammatqulovich; Asatova Sevinch Samad qizi; Gaybullayeva Gulchiroy Zavkijon qizi (Web of Journals Publishing, 2024)
The article presents an analysis of technological methods aimed at investigating the consequences of sanding in wells in the Kyzylkum region. The main causes of sanding and their impact on pump operation are considered, including damage to working parts, reduced pressure characteristics and increased frequency of repairs.
Keywords: Sand penetration, pumping equipment, intensity of sand removal from the formation, methods of reducing sand penetration in wells, equipment wear, optimisation of pumps operation.